NEBIVOLOL AND IRBESARTAN REDUCE POST-HEMODIALYSIS AND AMBULATORY BP IN PATIENTS WITH INTRADIALYTIC HYPERTENSION: A RANDOMIZED CROSS-OVER STUDY. (June 2018) - Bikos, A.; Loutradis, C.; Aggeloudi, E.; Karpetas, A.; Raptis, V.; Ginikopoulou, E.; Panagoutsos, S.; Pasadakis, P.; Balaskas, I.; Liakopoulos, V.; Papagianni, A.; Sarafidis, P.A.
Abstract : Objective: Blood pressure (BP) increase during or immediately after hemodialysis is an abnormal hemodynamic response to ultrafiltration and occurs in 5–20% of patients. Intradialytic hypertension is associated with adverse clinical outcomes and is often poorly diagnosed and controlled. This study aimed to evaluate the effects of nebivolol and irbesartan in 24hour ambulatory BP in hemodialysis patients with intradialytic hypertension. Design and method: This is a randomized cross-over study in 38 hemodialysis patients (age: 60.4 ± 11.1 years, male: 65.8%) with intradialytic hypertension, defined as mean intradialytic rise > = 10 mmHg in systolic BP (SBP) over 6 consecutive hemodialysis sessions. After baseline evaluation, patients were randomly assigned to nebivolol 5 mg and subsequently irbesartan 150 mg, or vice versa. Half of the patients received a single drug-dose 1 hour before hemodialysis (n = 19) or for a whole week, before evaluation (n = 19). A two-week wash-out period took place before the initiation of the second drug. All subjects underwent 24hour ambulatory BP monitoring starting before a midweek session. Results: In total, 20 (52.6%) patients received nebivolol first and 18 (47.4%) received irbesartan first. Patients receiving a single dose of either nebivolol or irbesartan had lower post-dialysis SBP and diastolic BP (DBP) [Baseline: 161.6 ± 16.3/95.4 ± 12.3; Nebivolol: 146.1 ± 20.4 (p = 0.003), 84.5 ± 11.8 (p < 0.001); Irbesartan: 144.7 ± 29.9 (p = 0.003), 86.8 ± 18.0 (p = 0.047) mmHg; respectively], non-significantly lower 24-hour SBP and lower DBP [Baseline: 147.8 ± 16.0/87.7 ± 11.9; Nebivolol: 144.0 ± 19.5 (p = 0.070), 83.3 ± 11.7 (p = 0.015); Irbesartan: 143.1 ± 21.7 (p = 0.171), 84.7 ± 12.8 (p = 0.095) mmHg]. Patients on weekly administration of either nebivolol or irbesartan had significantly lower post-dialysis SBP and DBP (Baseline: 167.1 ± 13.6/99.8 ± 10.6 Nebivolol: 145.2 ± 16.6 (p < 0.001), 91.0 ± 11.8 (p = 0.003); Irbesartan: 147.1 ± 23.8 (p = 0.002), 87.6 ± 12.5 (p = 0.001) mmHg), significantly lower 24-hour SBP and DBP (Baseline: 148.2 ± 12.5/91.7 ± 9.7 Nebivolol: 139.2 ± 10.4 (p < 0.001), 85.2 ± 7.7 (p = 0.001); Irbesartan: 142.9 ± 15.7 (p = 0.188), 85.5 ± 9.9 (p = 0.015) mmHg; accordingly) and significantly lower daytime and nighttime ambulatory SBP and DBP. No significant differences in BP reduction between nebivolol and irbesartan were observed. Conclusions: Both nebivolol and irbesartan reduce post-dialysis and 24-hour BP in patients with intradialytic hypertension. Weekly administration had greater effect and nebivolol seemed numerically slightly more potent than irbesartan; permanent administration of these agents may be more effective than pre-dialysis dosing.